2017
DOI: 10.3389/fmicb.2017.01430
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Major Sequence Types among Multidrug-Resistant Staphylococcus epidermidis Strains Isolated from Infected Eyes and Healthy Conjunctiva

Abstract: We examined the presence of virulence and antibiotic resistance genes, SCCmec types and determined the genomic diversity among ocular S. epidermidis isolates (patients-23, healthy controls-29). PCR determined the presence of antibiotic resistance genes, virulence genes and SCCmec types among all isolates. MLST and PFGE determined the genomic relatedness among them. All isolates of S. epidermidis showed resistance to at least one class of antibiotics of which 48 isolates were multidrug resistant and carried ARG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
12
1
Order By: Relevance
“…The IS 256, ica AB, and qac A/B genes were also highly prevalent among these isolates. All S. epidermidis isolates carried the mec A gene, which is similar to a study conducted in China (~96%) (Li et al, 2009 ), but higher compared to a study done in Portugal (~70%) (Rolo et al, 2012 ) and India (~67%) (Jena et al, 2017 ). The high degree of antimicrobial resistance and the presence of the mec A gene may indicate the presence of methicillin-resistant S. epidermidis (MRSE), which is more often resistant to other antimicrobials compared to methicillin-sensitive S. epidermidis (Otto, 2009 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The IS 256, ica AB, and qac A/B genes were also highly prevalent among these isolates. All S. epidermidis isolates carried the mec A gene, which is similar to a study conducted in China (~96%) (Li et al, 2009 ), but higher compared to a study done in Portugal (~70%) (Rolo et al, 2012 ) and India (~67%) (Jena et al, 2017 ). The high degree of antimicrobial resistance and the presence of the mec A gene may indicate the presence of methicillin-resistant S. epidermidis (MRSE), which is more often resistant to other antimicrobials compared to methicillin-sensitive S. epidermidis (Otto, 2009 ).…”
Section: Discussionsupporting
confidence: 82%
“…The hospital environment is known to play a fundamental role in the amplification and the diversification of SCC mec elements in S. epidermidis (Rolo et al, 2012 ). S. epidermidis harbouring multiple ccr and mec gene complexes have been extensively reported in the literature (Ibrahem et al, 2008 ; Garza-González et al, 2010 ; Svensson et al, 2011 ; Zong et al, 2011 ; Rolo et al, 2012 ; Jena et al, 2017 ), but none of these studies have addressed the possibility of polyclonality. Polyclonality among S. epidermidis isolates has been reported in prosthetic joint infections (Galdbart et al, 1999 ), prosthetic valve endocarditis (Van Wijngaerden et al, 1997 ; Jena et al, 2017 ), healthy ocular surfaces (Ueta et al, 2007 ), and CRBSI (Rijnders et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications suggest that resistance and virulence may be converging and that SCCmec types associated with community-acquired staphylococci are now exhibiting increased antibiotic resistance [16,19,20,28,[40][41][42]. Despite the predominance of SCCmec types IV/V among MRSE in the current study (n = 6), nearly all (83%) showed MDR.…”
Section: Discussioncontrasting
confidence: 55%
“…These findings are consistent with those from an analysis of 30 MRSE isolates from ocular infections in Sao Paulo, Brazil, which found that of 17 isolates containing SCCmec IV/V, at least 70% were MDR [19]. Similarly, Jena et al examined the molecular traits of 52 ocular S. epidermidis isolates (23 from infections and 29 from asymptomatic healthy conjunctiva) in India and determined that all isolates containing SCCmec IV/V (10 from infections; 11 from healthy conjunctiva) were MDR [20]. Consistent with results reported from health-care settings, an analysis of 643 staphylococci isolated from environmental samples in a community in the UK found that of 46 CoNS isolates for which SCCmec types were determined, 18 were type IV/V, and 16 of these demonstrated resistance to 3 or more antibiotics [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation